PENGARUH PROFIBILITAS DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Agustami, Silviana; Hidayat, Syarif (Jurnal Riset Akuntansi dan Keuangan, 2015)
The pulp paper industry in CSR disclosure has been heavily criticized because it often advertises itself but does not match performance. This research is generally intended to know the effect of profitability and environmental performance on the disclosure of social responsibility on the pulp paper and wood industries listed on BEI 2010-2013. The research method used is the method of causality research using two data collection techniques, namely through literature review and secondary data collection. The results obtained are as follows: 1. Profitability in the pulp paper and wood industry in BEI 2010-2013 is not good because the average every year always suffered losses, 2. Environmental performance in the pulp paper and wood industry in BEI 2010-2013 Is good enough, 3. Disclosure of responsibility on pulp paper and wood industry in BEI 2010-2013 is good enough, 4. There is a positive effect of profitability on corporate social responsibility disclosure, 5. There is a positive influence of environmental performance on the disclosure of social responsibility company. From these results can be concluded that based on regression calculation results obtained a positive effect between profitability and environmental performance on corporate social responsibility disclosure.